2021
DOI: 10.1108/ijchm-12-2020-1403
|View full text |Cite
|
Sign up to set email alerts
|

Using social distancing technology in hotels: a social exchange perspective

Abstract: Purpose As social distancing procedures can be facilitated by various hotel technologies, the purpose of this paper is to investigate the extent to which consumers develop perceptions of value regarding the use of certain hotel technologies for social distancing in hotels. Design/methodology/approach Drawing from the social exchange theory, this study conceptualized the benefits of using technologies for social distancing, health risks, social rewards and privacy concerns as antecedents of value of using tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…Similarly, despite some focus on topics such as food safety (MacLaurin, 2001; Tarulevicz and Ooi, 2021), healthy eating (Al-Ansi et al , 2022; Jeong et al , 2019), hotel cleanliness (Zemke et al , 2015) and hotel safety during COVID-19 (Choi et al , 2022; Morosan and DeFranco, 2021), no hospitality studies appear to have addressed travel medicine thus far. Only a handful of papers in travel medicine journals have mentioned hotel guests’ health; most have covered food and waterborne infectious diseases such as diarrhea, norovirus, malaria, Legionnaires’ disease and COVID-19 (Erdogan and Arslan, 2007; Leshem et al , 2016; Fan et al , 2021); however, as confirmed by the pandemic’s devastating blow to tourism and hospitality, safety and health are of paramount importance in consumer-centered sectors (Wilks and Oldenburg, 1995; Maher et al , 2022).…”
Section: Travel Medicinementioning
confidence: 99%
“…Similarly, despite some focus on topics such as food safety (MacLaurin, 2001; Tarulevicz and Ooi, 2021), healthy eating (Al-Ansi et al , 2022; Jeong et al , 2019), hotel cleanliness (Zemke et al , 2015) and hotel safety during COVID-19 (Choi et al , 2022; Morosan and DeFranco, 2021), no hospitality studies appear to have addressed travel medicine thus far. Only a handful of papers in travel medicine journals have mentioned hotel guests’ health; most have covered food and waterborne infectious diseases such as diarrhea, norovirus, malaria, Legionnaires’ disease and COVID-19 (Erdogan and Arslan, 2007; Leshem et al , 2016; Fan et al , 2021); however, as confirmed by the pandemic’s devastating blow to tourism and hospitality, safety and health are of paramount importance in consumer-centered sectors (Wilks and Oldenburg, 1995; Maher et al , 2022).…”
Section: Travel Medicinementioning
confidence: 99%
“…Social factors contribute to a consumer's decision-making and perception of a specific behavior by influencing their expectations and perceptions of others (e.g. friends, family and colleagues) (Morosan and DeFranco, 2021). In addition to one's attitude toward a high-technology product, socialization forces related to following the norms of the referent group also influence consumer adoption (Morosan, 2021).…”
Section: Normative Influence and Social Influencementioning
confidence: 99%